Enhanced Associations With Actions of the Artist Influence Gaze Behaviour. (March 2020) - Williams, Louis; McSorley, Eugene; McCloy, Rachel
The aesthetic experience of the perceiver of art has been suggested to relate to the art-making process of the artist. The artist's gestures during the creation process have been stated to influence the perceiver's art-viewing experience. However, limited studies explore the art-viewing experience in relation to the creative process of the artist. We introduced eye-tracking measures to further establish how congruent actions with the artist influence perceiver's gaze behaviour. Experiments 1 and 2 showed that simultaneous congruent and incongruent actions do not influence gaze behaviour. However, brushstroke paintings were found to be more pleasing than pointillism paintings. In Experiment 3, participants were trained to associate painting actions with hand primes to enhance visuomotor and visuovisual associations with the artist's actions. A greater amount of time was spent fixating brushstroke paintings when presented with a congruent prime compared with an incongruent prime, and fewer fixations were made to these styles of paintings when presented with an incongruent prime. The results suggest that explicit links that allow perceivers to resonate with the artist's actions lead to greater exploration of preferred artwork styles.